ANALYSIS OF FACTORS INFLUENCING THE OCCURRENCE OF RHEUMATIC HEART DISEASE (RHD) AMONG CHILDREN IN TOKULULI VILLAGE, RAILAKO ADMINISTRATIVE POST, ERMERA MUNICIPALITY, TIMOR-LESTE - Rima Evarianti; Me. Dulce Maria Guterres; Francelina N M do ego (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
Rheumatic Heart Disease (RHD) is a chronic cardiac condition that develops as a long-term complication of acute rheumatic fever resulting from inadequately treated streptococcal infections. This disease remains a significant child health problem in developing countries, including Timor-Leste, particularly in rural areas with limited environmental conditions and healthcare services. This study aimed to describe the occurrence of Rheumatic Heart Disease (RHD) among children and the associated contextual factors in Tokululi Village, Railako Administrative Post, Ermera Municipality, Timor-Leste. This study employed a descriptive quantitative design with a cross-sectional approach. The accessible population consisted of all parents or guardians of school-aged children in Marobo Hamlet, Tokululi Village, with a total of 100 respondents included using a total sampling technique. Data were collected through structured interviews using a questionnaire to assess family socioeconomic status, residential environmental conditions, access to and utilization of healthcare services, as well as family knowledge and health-related behaviors concerning child health. Data on RHD occurrence were obtained from health service records at the community health center based on diagnoses made by healthcare professionals. Data analysis was conducted descriptively (univariate), with results presented as frequency distributions and percentages. The results showed that in 2025, two cases of Rheumatic Heart Disease (RHD) among children were identified (2.0%). The majority of respondent families were classified as having a middle socioeconomic status (44.0%). Most residential environments were categorized as having moderate (41.0%) to good (36.0%) quality. Access to and utilization of healthcare services were generally considered adequate (85.0%). Family knowledge regarding child health was predominantly at a moderate (47.0%) and low (44.0%) level, while family health-related behaviors were mostly classified as good (62.0%). These findings indicate that although the identified occurrence of RHD was relatively low, environmental conditions, healthcare service factors, and family knowledge may potentially influence delays in disease detection and prevention. In conclusion, RHD among children in Tokululi Village remains present and requires continued attention, particularly given the limited diagnostic facilities at the primary healthcare level. Socioeconomic status, environmental conditions, access to healthcare services, and family knowledge and behaviors represent important contextual factors accompanying the occurrence of RHD among children. Strengthening primary and secondary prevention efforts, improving family health literacy, and reinforcing community-based healthcare systems are necessary to prevent the progression of RHD among children in rural areas. Keywords: Rheumatic Heart Disease; children; family factors; environment; healthcare services; Timor-Leste